The Reality of the Sacred in Mircea Eliade’s Phenomenology of Religion - Sully, Elmi Hamidah; Arifuddin, Nawawi Bahar; Truna, Dody S.; Rosyad, Rifki (PT. Hafasy Dwi Nawasena, 2026)
Mircea Eliade was a Romanian historian of religion and philosopher from Bucharest. He became influential in religious studies during the 20th century, focusing on the importance of myths and symbols in human experience. Notable works include